2014
DOI: 10.1002/dmrr.2536
|View full text |Cite
|
Sign up to set email alerts
|

Improved pharmacokinetic and pharmacodynamic profiles of insulin analogues using InsuPatch, a local heating device

Abstract: The use of the heating device upon administration of short-acting insulin analogues in pump-treated type 1 diabetic patients was found to enhance insulin absorption. This heating device may therefore serve to achieve better meal insulin coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…Hexamer lifetimes may thus be measured via the progressive disappearance of the d-d optical transitions characteristics of the tetrahedral Co 2ϩ -coordination site in R 6 hexamers. 11 Fitting of the time-dependent attenuation of the 574-nm Co 2ϩ band intensity indicated that the 11 Tetrahedrally coordinated Co 2ϩ provides an absorption spectrum in the visible range due to d-d transitions in its incomplete d-shell; this band is negligible in an octahedral complex (32).…”
Section: A2mentioning
confidence: 99%
“…Hexamer lifetimes may thus be measured via the progressive disappearance of the d-d optical transitions characteristics of the tetrahedral Co 2ϩ -coordination site in R 6 hexamers. 11 Fitting of the time-dependent attenuation of the 574-nm Co 2ϩ band intensity indicated that the 11 Tetrahedrally coordinated Co 2ϩ provides an absorption spectrum in the visible range due to d-d transitions in its incomplete d-shell; this band is negligible in an octahedral complex (32).…”
Section: A2mentioning
confidence: 99%
“…Clinical trials have been conducted with an InsuPatch device heating the injection site and increasing blood supply, which resulted in more rapid insulin absorption. This device might be integrated with an insulin pump thus improving the functioning of the pump [6][7][8].…”
Section: Rapid-acting Insulinmentioning
confidence: 99%
“…Insulin-loaded microemulsions are currently the most effective, although they are still in the preclinical phase. The patches contain 10% oleic acid, 38% aqueous phase, and 50% surfactant with 2% dimethyl sulfoxide [6,36].…”
Section: Insulin Patchesmentioning
confidence: 99%
See 2 more Smart Citations